National Parliament Government Center - Tabaquero, Eduardo A. Jr. (Manila : National University, 2005)
Since the early 90's, the Congress of the Philippines has been trying to push through the Charter Change that would process the amending of the Article VI of the constitution. Presently, a newly $1 (Belected president, Gloria Macapagal $1 (BArroyo, was sworn in to office and started her government with the support for the amending of the constitution that would shift the current Presidential Government to the creation of a Federal system of government and the adoption of a Parliamentary Form of government that is envisioned to make each region of the country autonomous and progressive. Whereas, majority of the countries in the world, particularly the developing countries and the s
Chapter I. Introduction -- Chapter II. Methodology -- Chapter III. Terms of references -- Chapter IV. Design framework -- Chapter V. Design analysis and presentation -- Chapter VI. Conclusion and recommendation -- Bibliography -- Pictorial Presentation -- Appendices/Annexes -- Profile of proponent.
Includes bibliographical references.